SIRT1 Suppresses β-amyloid Production by Activating the α-Secretase Gene ADAM10 - Donmez, Gizem (2010)
A hallmark of Alzheimer's disease (AD) is the accumulation of plaques of Aβ 1-40 and 1-42 peptides, which result from the sequential cleavage of APP by the β and γ-secretases. The production of Aβ peptides is avoided by alternate cleavage of APP by the α and γ-secretases. Here we show that production of β-amyloid and plaques in a mouse model of AD are reduced by overexpressing the NAD-dependent deacetylase SIRT1 in brain, and are increased by knocking out SIRT1 in brain. SIRT1 directly activates the transcription of the gene encoding the α-secretase, ADAM10. SIRT1 deacetylates and coactivates the retinoic acid receptor β, a known regulator of ADAM10 transcription. ADAM10 activation by SIRT1 also induces the Notch pathway, which is known to repair neuronal damage in the brain. Our findings indicate SIRT1 activation is a viable strategy to combat AD, and perhaps other neurodegenerative diseases.